Recent developments and inventive approaches in vertical farming - Sowmya, Chennu; Anand, M.; Indu Rani, C.; Amuthaselvi, G.; Janaki, P. (Frontiers in Sustainable Food Systems, 2024)
Biomimicry" is an acronym used to describe how people looked at nature for inspiration to tackle a variety of problems. The modern problems of fast-increasing urbanization, land degradation, climate change, pandemics, loss of biodiversity, and widespread use of pesticides and fertilizers seriously threaten our food supply chain. There is a growing consumer demand for nutrient-dense, flavourful plant-based cuisine with minimal environmental impact. Moreover, a considerable portion of food roughly 24% is lost before it reaches consumers, partly as a result of poor quality and protracted supply chains. Researching new methods of producing food is essential since, by 2050, there will be more than 9.7 billion people on the planet, 70% of whom will reside in cities. Vertical farming (VF), which relieves pressure on conventional agricultural land by using vertical space instead of horizontal expansion, is growing in popularity as a solution to these problems. Because VF incorporates soil-less growth techniques, it is well-suited for urban environments. This strategy may help to produce more premium products, such as fruits, vegetables, flowers, and herbs. It may also help to produce cosmetics and medications made from plants. Vertical farming, is becoming more favoured as an alternative to traditional agriculture, and provides avenues for enhancing sustainable food production given the growing challenges of climate change and population growth.